New Entrants in the Pandemic Era: An Empirical Study on Factors Affecting Start-Up Businesses in The Cities of the Philippines - Mary Matthew N. Jamer; Aicille Purisima; John Robert M. Olvido; Mara R. Broqueza; Joseph C. Reyes (Camarines Sur Polytechnic Colleges, 2024)
The study's purpose was to assess the factors influencing the establishment of startup businesses in Philippine Cities during the pandemic. To achieve this, a quantitative method employing a causal explanatory research design was utilized. The study relied on data from the cities and municipalities competitive index (CMCI), which were then analyzed using the Pearson Correlation Coefficient and Multiple linear regression. The findings of the study revealed a positive and significant relationship between newly approved businesses and four variables: the number of banks, the presence of a business-one-stop-shop (boss) operating throughout the year, the availability of broadband services, and the presence of transportation options. These factors were shown to have a significant impact on the establishment of startup businesses in Philippine cities. Regression analysis identified local inflation rate, number of banks, and transportation options as significant predictors of startup businesses in Philippine cities. A 1% increase in the inflation rate resulted in a 69.286 decrease in startups. Based on these factors, the study concluded that launching a business during the pandemic was found to be exceedingly challenging, with existing startups facing greater vulnerability to COVID-19 shocks compared to established businesses. This study highlighted the challenges faced by startups during the pandemic and emphasized the importance of factors like financial access, streamlined registration processes, reliable internet, transportation infrastructure, and inflation rates. Understanding these factors is vital for policymakers and entrepreneurs striving to foster startup establishment and growth in Philippine cities during challenging times.